Relationship Between Radiomics and Risk of Lymph Node Metastasis in Pancreatic Ductal Adenocarcinoma. Issue 9 (October 2019) - Bian, Yun; Guo, Shiwei; Jiang, Hui; Gao, Suizhi; Shao, Chenwei; Cao, Kai; Fang, Xu; Li, Jing; Wang, Li; Hua, Wenda; Zheng, Jianming; Jin, Gang; et al.
Abstract : Objective: The objective of this study was to explore the exact relationship between the arterial radiomics score (rad-score) and lymph node (LN) metastasis in pancreatic ductal adenocarcinoma (PDAC). Methods: A total of 225 patients with pathologically confirmed PDAC who underwent multislice computed tomography within 1 month of resection from December 2016 to August 2017 were retrospectively studied. For each patient, 1029 radiomics features of arterial phase were extracted, which were reduced using the least absolute shrinkage and selection operator logistic regression algorithm. Multivariate logistic regression models were used to analyze the association between the arterial rad-score and LN metastasis. Results: Lymph node–negative and LN-positive patients accounted for 107 (47.56%) and 118 (52.44%) of the cohort, respectively. The rad-score, which consisted of 12 selected features of the arterial phase, was significantly associated with LN status ( P < 0.05). Univariate analysis revealed that the arterial rad-score and T stage were independently and positively associated with risk of LN metastasis ( P < 0.05). Multivariate analyses revealed a significant association between the arterial rad-score and the LN metastasis ( P < 0.0001). Higher arterial rad-score was associated with LN metastasis ( P for trend <0.0001). Conclusions: The arterial rad-score is independently and positively associated with the risk of LN metastasis in PDAC. Abstract : Supplemental digital content is available in the text.